Increased risk of virologic failure to the first antiretroviral regimen in HIV-infected migrants compared to natives: data from the ICONA cohort. (March 2016) - Saracino, A.; Lorenzini, P.; Lo Caputo, S.; Girardi, E.; Castelli, F.; Bonfanti, P.; Rusconi, S.; Caramello, P.; Abrescia, N.; Mussini, C.; Monno, L.; d'Arminio Monforte, A.; et al.
Abstract: Migrant and Italian HIV-infected patients ( n  = 5773) enrolled in the ICONA cohort in 2004–2014 were compared for disparities in access to an initial antiretroviral regimen and/or risk of virologic failure (VF), and determinants of failure were evaluated. Variables associated with initiating antiretroviral therapy (ART) were analysed. Primary endpoint was time to failure after at least 6 months of ART and was defined as: VF, first of two consecutive virus loads (VL) >200 copies/mL; treatment discontinuation (TD) for any reason; and treatment failure as confirmed VL >200 copies/mL or TD. A Poisson multivariable analysis was performed to control for confounders. Migrants presented significantly lower CD4 counts and more frequent AIDS events at baseline. When adjusting for baseline confounders, migrants presented a lower likelihood to begin ART (odds ratio 0.80, 95% confidence interval (CI) 0.67–0.95, p 0.012). After initiating ART, the incidence VF rate was 6.4 per 100 person-years (95% CI 4.8–8.5) in migrants and 2.7 in natives (95% CI 2.2–3.3). Multivariable analysis confirmed that migrants had a higher risk of VF (incidence rate ratio 1.90, 95% CI 1.25–2.91, p 0.003) and treatment failure (incidence rate ratio 1.16, 95% CI 1.01–1.33, p 0.031), with no differences for TD. Among migrants, variables associated with VF were age, unemployment and use of a boosted protease inhibitor–based regimen versus nonnucleoside reverse transcriptase inhibitors. Despite the use of more potent and safer drugs in the last 10 years, and even in a universal health care setting, migrants living with HIV still present barriers to initiating ART and an increased risk of VF compared to natives.